INCLUSIVE EDUCATION: ENSURING EQUAL LEARNING OPPORTUNITIES FOR ALL (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Inclusive education has become a fundamental principle of modern educational systems worldwide. It aims to provide equal learning opportunities for all students regardless of their physical, intellectual, social, emotional, linguistic, or other differences. Inclusive education promotes diversity, equity, and participation while ensuring that every learner has access to quality education within mainstream educational settings. This paper examines the concept of inclusive education, its benefits, challenges, and strategies for effective implementation. The study highlights the importance of supportive policies, teacher training, and collaborative practices in creating inclusive learning environments. The findings suggest that inclusive education not only benefits students with special educational needs but also contributes to the development of more equitable and socially cohesive societies.